3(3y + 2) + 8y 9y + 6 + 8y 17y + 6
9x + 17y since no values were given for the x and y then it can not be evaulated.
17
As written, that's 17y + 4 which is in its simplest form. -6y^2 + 23y + 4 factors to (4 - y)(1 + 6y)
6x12=72+654=726+555= 1281
If: 6+17y = 15+14y then 17y-14y = 15-6 so 3y = 9 and then y = 3
3(3y + 2) + 8y 9y + 6 + 8y 17y + 6
9x + 17y since no values were given for the x and y then it can not be evaulated.
17
6y2+17y-14 = (2x+7)(3x-2) when factored
-17 + y,,must be equals to..-17y..
-17 + y,,must be equals to..-17y..
It is an algebraic expression which can be simplified if the plus or minus value of 47y was given.
As written, that's 17y + 4 which is in its simplest form. -6y^2 + 23y + 4 factors to (4 - y)(1 + 6y)
Since the bigger number is the one we have to take from the smaller one, the answer is apt to be a negative. So 17y - 18y = - 1y
132
6x12=72+654=726+555= 1281